2010
DOI: 10.5539/mas.v4n5p125
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Catalytic Activity of Nanostructure Mn2O3 Prepared by Solvent-thermal Method on Degrading Crystal Violet

Abstract: Nanostructure manganese oxide shows very good catalytic activity in waste water treatment of dyeing industry. A few nano manganese oxides are prepared through different methods, Their catalytic degradation property of dyeing material (crystal violet solution) is tested with H 2 O 2 as oxidizer. Besides, the influence of other parameters are also studied, including catalyst dosage, H 2 O 2 dosage and catalyst circulation. After reaction of 60 minutes, degradation of crystal violet can reach over 99% for most ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…This observation is mainly due to the increase in the number of active sites on the catalyst surface which are affected by the increase in the catalyst dosage. This finding was consistent with Su et al [42], who found that when the catalyst dosage is increased, it would also increase the catalytic activity. Therefore, the catalyst dosage trend for CO 2 conversion was 3 < 5 < 7 g.…”
Section: Effect Of Catalyst Dosagesupporting
confidence: 92%
“…This observation is mainly due to the increase in the number of active sites on the catalyst surface which are affected by the increase in the catalyst dosage. This finding was consistent with Su et al [42], who found that when the catalyst dosage is increased, it would also increase the catalytic activity. Therefore, the catalyst dosage trend for CO 2 conversion was 3 < 5 < 7 g.…”
Section: Effect Of Catalyst Dosagesupporting
confidence: 92%
“…The use of MnO 2 as a photocatalyst has become increasingly common in recent years . Recently, manganese­(IV) oxide has sparked a lot of interest in photocatalytic applications because of its crystallinity, large surface area, and ability to disintegrate water molecules into hydrogen and hydrogen ions. Furthermore, even at low temperatures, manganese dioxide has a high catalytic ability . It is reported that MnO 2 is one of the most feasible inorganic semiconductors for antibacterial actions due to physical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Like many other basic dyes, CV is toxic and poses a threat to the environment [14]. Metal oxide catalysts employed so far for the removal/degradation of this dye include ZnO [15], Fe 3 O 4 [16], polytungstonickelate [17] and nano-Mn 3 O 4 [18]. All of these studies suggest a Fenton-type oxidation mechanism proceeding through hydroxyl radicals generated by photocatalysis or from peroxide [19,20].…”
Section: Introductionmentioning
confidence: 99%